Enterprising Women : Toward Equal Business Opportunity in Southeast Asia - World Bank (Washington, DC, 2022)
This report explores gender differences in entrepreneurship for micro, small, and medium enterprises (MSME) in Southeast Asia. It analyzes data from five Southeast Asian countries: Cambodia, Indonesia, Lao People’s Democratic Republic (Lao PDR), Timor-Leste, and Vietnam, and reviews existing evidence from across the region. Using data from household and firm-level surveys, the report establishes stylized facts about gender gaps in participation in entrepreneurship and in business performance for two types of businesses: microbusinesses and small and medium enterprises (SME). Microbusinesses include businesses with less than 5 employees, and SMEs include businesses with between 5 and 100 employees. This study focuses on MSMEs because they account for 97 percent of all enterprises in Asia-Pacific Economic Cooperation countries and because the owner’s gender may have a greater influence on the outcomes of MSMEs than large businesses, which are more likely to have multiple owners or be part of a larger corporation. After establishing stylized facts about gender gaps in entrepreneurship, the report employs various econometric. techniques to understand better the factors that are associated with these gaps. Finally, the report makes a case for policy action and presents a review of global evidence on how these factors are best addressed.